Analysis of Junior High School Teacher Readiness in Implementing the Independent Curriculum - Rahayuningsih, Suesthi; Doni Uji, Windiatmoko; Achmad, Rijanto (Jurnal Pendidikan Edutama, 2024)
In the 2022/2023 academic year, the independent curriculum will be implemented simultaneously, including in Mojokerto Regency. This study aims to analyze the readiness of teachers in implementing the independent curriculum in Mojokerto, especially at the junior high school level. This type of research, descriptive research with survey method. The survey reveals teacher readiness in terms of knowledge and attitude. Knowledge related to knowledge of independent curriculum policies, independent curriculum structure, learning and assessment as well as the Pancasila Student Profile Strengthening Project, while attitudes related to attitudes taken by teachers in preparing the implementation of an independent curriculum. Respondents in this study were junior high school teachers in Mojokerto. The results obtained were teacher readiness in the aspect of knowledge with the 10 questions given to respondents obtained that all questions gave positive responses knowing and very knowing more than 50%, and there were 2 questions which answered 100% knowing and very knowing related to Pancasila Student Profile Strengthening Project, Learning Achievements, Learning Objectives, and Learning Objective Flow. And teacher readiness from the Attitude Aspect with 12 questions given to respondents obtained 11 questions giving positive and very positive responses with a percentage of more than 50%, and there is one question, namely how often to compose learning assessments in an independent curriculum less than 50%, namely 43%. From these results, more than 50% of teachers were ready to implement the independent curriculum in terms of knowledge and attitudes.